2019
DOI: 10.30598//ijcr.2019.7-sun
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penambahan Carboxymethyl Cellulose Terhadap Karakteristik Bioplastik Dari Pati Ubi Nagara (Ipomoea batatas L.)

Abstract: Synthesis and characterization of bioplastics from Nagara sweet potatoes (Ipomoea batatas L) starch with carboxymethyl cellulose (CMC) as a filler has been conducted. The purpose of this study was to evaluate the effects of CMC addition on the characteristic of bioplastics from Nagara sweet potato (Ipomoea batatas L) starch. Bioplastic synthesis was carried out by the melt intercalation method with variations in the amount of CMC 0-30% (w/w). Bioplastics were analyzed using FTIR spectrophotometer, thickness, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
0
4
0
3
Order By: Relevance
“…This is consistent with the equation stating that energy is directly proportional to wavelength, and the more stable the molecule, the lower the energy produced. According to the theory developed, it can be deduced that the energy and molecular stability increase with kepok banana blossom filler concentration in the edible film [18].…”
Section: 2mentioning
confidence: 99%
“…This is consistent with the equation stating that energy is directly proportional to wavelength, and the more stable the molecule, the lower the energy produced. According to the theory developed, it can be deduced that the energy and molecular stability increase with kepok banana blossom filler concentration in the edible film [18].…”
Section: 2mentioning
confidence: 99%
“…This is in accordance with the formula that energy is directly proportional to the wavelength, the more stable a molecule come from the lower the energy produced. Based on the theory that has been obtained, it can be concluded that the bigger the concentration of kepok banana blossom filler in the edible film it would make the greater the energy and stability of a molecule [19].…”
Section: Analysis Of Fourier Transform Infra Red (Ft-ir)mentioning
confidence: 99%
“…Karakteristik dari plastik biodegradable yang didapatkan dari penelitian ini lebih unggul dari penelitian sebelumnya menggunakan proses yang sama dengan bahan baku selulosa dari tandan kosong kelapa sawit dan pati mendapatkan kuat tarik maksimum 6,27 kPa (0,00627 MPa) [12]. Penelitian dengan bahan baku CMC dan pati ubi nagara dengan hasil kuat tarik tertinggi pada 0,5281 MPa namun elongasi yang didapatkan lebih tinggi yaitu sebesar 116,1 % [21]. Penelitian dengan bahan baku pati biji mangga dan selulosa mendapatkan kuat tarik optimum pada 6,2551 MPa, terdegradasi dalam 26 hari, namun dengan elongasi yang lebih tinggi yaitu 13,433% [22].…”
Section: Hasil Uji Mutu Plastik Biodegradableunclassified